Effects of Schema-Based Instruction on Immediate, Generalized, and Combined Structured Word Problems. (August 2020) - Peltier, Corey; Sinclair, Tracy E.; Pulos, Joshua M.; Suk, Andrea
Instruction targeting the underlying math problem structure is identified as an evidence-based practice for students with a specific learning disability (SLD). Furthermore, schema-based instruction is identified as a potentially evidence-based practice for students with a SLD. This study extended prior work by (a) using a teacher as the implementer, (b) evaluating the efficacy of an adaptable intervention, and (c) evaluating student performance on generalized and combined schema structure problems. The participants included 12 fourth- and fifth-grade students with a disability and receiving supplemental mathematics instruction in a resource room setting. The intervention package consisted of a problem-solving mnemonic and schema-based instruction for mathematics. A multiple-probe design across participant groups was used to establish a functional relation. Students improved performance on word problems representing simple, generalized, and combined schema structures. The aggregated Tau-U effect size (ES) for this study was 95% (CI90 [83%, 100%]) and the aggregated between-case standardized mean difference (BC-SMD) was 3.05 (CI95 [2.54, 3.60]).